Efficacy of aqueous and oil formulations of a specific Metarhizium anisopliae isolate against Aphis craccivora Koch, 1854 (Hemiptera: Aphididae) under field conditions - Nweke, A.; Akutse, K.S.; Ulrichs, C.; Fiaboe, K.K.M.; Maniania, N.K.; Ekesi, S. (Wiley, 2019)
Cowpea (Vigna unguiculata) production is constrained by biotic and abiotic factors, among which Cowpea aphid (Aphis craccivora) is ranked a key insect pest that severely limits its potential for provision of food and nutritional security to millions of people in sub‐Saharan Africa. The use of entomopathogenic fungi for A. craccivora management has been recently demonstrated at laboratory and field levels as alternative to synthetic insecticides, but with low adoption in Africa. This study assessed the efficacy of aqueous and oil formulations of Metarhizium anisopliae ICIPE 62 against A. craccivora under field conditions. Metarhizium anisopliae formulations and a commonly used insecticide Duduthrin® were applied using knapsack sprayers with target output of 350 L/ha. Data on aphid infestation levels were collected weekly. ICIPE 62 efficacy in inducing mortality was also assessed 24 hr post‐treatment coupled with mycosis test. Further, leaf and grain yields were determined. After six weeks post‐treatment in the wet season, there was no significant reduction in aphid density in fungus‐treated plots compared to control and Duduthrin®‐treated plots. However, in the dry season six weeks after applying the treatments, oil formulation spray resulted low aphid density compared to control and Duduthrin®‐treated plots. ICIPE 62 formulations did not negatively affect the natural enemies’ population. Leaf yield from the various treatments did not differ significantly in the wet season, but the two fungal formulations recorded higher yields in dry season compared to other treatments. Grain yields in wet and dry seasons were lower in control and Duduthrin®‐treated plots compared to both ICIPE 62 formulations. This study showed that both M. anisopliae ICIPE 62 formulations are effective in suppressing A. craccivora population under field conditions without adverse effects on its beneficial insects. The study also revealed that efficacy of fungal‐based biopesticides is highly dependent on environmental conditions.